Less myth, more measurement: Decomposing excess returns from the 1989 minimum wage hike - Carl Lin (Institute for the Study of Labor (IZA), 2012)
In the book Myth and Measurement, Card and Krueger (1995) examine the economic impact of the 1989 minimum wage hike on the welfare of 110 firms which employ a disproportionate number of minimum-wage workers. Their results show mixed evidence that excess returns associated with news about the 1989 minimum-wage legislation. This paper re-examines this question by decomposing excess returns. Our simple and intuitive approach attributes excess returns to either differences in market performances (economy-wide factors) or firm-specific traits (individualistic factors). We likewise show that, generally, minimum wage legislation had little or no effect on employer wealth. However, by decomposing total excess returns, we find that the apparent lack of an effect is a consequence of two off-setting forces: (1) a negative effect arising from firm-specific traits (adverse information on minimum-wage worker employers) and (2) a positive effect arising from market performance. In other words, we show that while the aggregate effect of the 1989 minimum wage hike was neutral, there was a significant negative impact on firms that was neutralized by positive market performance.
urn:nbn:de:101:1-201203063989
Keywords: G14; J31; J38; 330; minimum wage; excess returns; decomposition; Mindestlohn; Wirkungsanalyse; Kapitalertrag; Unternehmenserfolg; Dekompositionsverfahren; Schätzung; USA